UHPLC-DAD characterization of bioactive secondary metabolites from Ocimum americanum and Pupalia lappacea extracts: Antioxidant activity and antihypertensive effects on L-NAME-induced hypertensive rats - LAGNIKA, LATIFOU (My University, 2019)
Ocimum americanum L. (Lamiaceae) and Pupalia lappacea (L) Juss. (Amaranthaceae) are two plants used in Bénin to manage hypertension. Little scientific data is available on the antihypertensive properties of these plants. Therefore, we investigated the antihypertensive potential of ethanolic extracts of O. americanum and P. lappacea on L-NAME-induced hypertensive rats. The DPPH free radical scavenging potential, Fe3+ reducing capacity, superoxide anion radical and hydrogen peroxide scavenging were assessed. Extracts were also screened for their active compounds using ultimate high-performance liquid chromatography 3000. CODA™ non-invasive blood pressure system was used to record blood pression parameters. Both extracts induced significant decrease of systolic, diastolic blood pressure and mean arterial pression. O. americanum extract at 250 mg/kg body weight, decreased mean blood pressure (MBP) from 146 ± 4.80 to 98.4 ± 9.44 mmHg and P. lappacea extract from 154.4 ± 11.28 to 111.8 ± 9.44 mmHg. A significant decrease of MBP was also observed with Losartan and Captopril at 100 mg/kg body weight. P. lappacea showed the higest ferric reducing/antioxidant power 4905 ± 87.79 μmol AAE g-1. Superoxide anion and hydrogen peroxide scavenging activities showed higher activity, 68.42 ± 3.68 and 38.68 ± 4.18%, respectively for O. americanum. The chromatography analysis of extracts suggested the presence of ferulic acid, chlorogenic, tannic, ellargic, caffeic acids and chrysin, rutin and isorhamnetin. The obtained results justify the traditional use of O. americanum and P. lappacea in management of hypertension in southern Bénin.
Keywords: Ocimum americanum; Pupalia lappacea; antihypertensive activity; antioxidant activity.